2020
DOI: 10.1186/s12891-020-3095-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of spinal brace/orthosis treatment for adults with scoliosis between 1967 and 2018: clinical outcomes and harms data

Abstract: Background: There is a paucity of literature regarding the conservative management of adult scoliosis. The authors review and summarize the literature from 1967 to 2018 on the clinical outcomes of spinal brace/orthosis use in this subgroup of the population. Methods: CINAHL, Embase, CENTRAL, PubMed and PEDro were searched from database inception to the 30th of October, 2018. A combination of medical subject heading terms and keywords pertaining to three core concepts (adult, scoliosis, and braces/orthoses) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…A 2016 prospective study with a sample size of 158 patients demonstrated this with 80% of their brace wearers showing unchanged or improved Cobb angles after adhering to bracing for around 8.5 years [ 80 ]. However, these results do not represent a statistically significant trend across similar studies [ 79 ]. There are plenty of adult scoliosis cases where patients continue to deteriorate despite the use of bracing [ 79 ].…”
Section: Spinal Deformity—scoliosiscontrasting
confidence: 58%
See 2 more Smart Citations
“…A 2016 prospective study with a sample size of 158 patients demonstrated this with 80% of their brace wearers showing unchanged or improved Cobb angles after adhering to bracing for around 8.5 years [ 80 ]. However, these results do not represent a statistically significant trend across similar studies [ 79 ]. There are plenty of adult scoliosis cases where patients continue to deteriorate despite the use of bracing [ 79 ].…”
Section: Spinal Deformity—scoliosiscontrasting
confidence: 58%
“…However, these results do not represent a statistically significant trend across similar studies [ 79 ]. There are plenty of adult scoliosis cases where patients continue to deteriorate despite the use of bracing [ 79 ]. Higher-quality studies and specifically randomized control trials (RCTs) are needed to determine bracing’s true utility in treating adult scoliosis, as there are not yet enough reliable findings to suggest their use beyond improving pain levels and function.…”
Section: Spinal Deformity—scoliosiscontrasting
confidence: 58%
See 1 more Smart Citation
“…objective is to describe the existing technologies in order to develop corrective orthoses and their applicability. The current statistical studies [5,9,10] have determined that there is no adequate evidence to reach one concurrent decision about what type of brace is the best among all other types. The adequacy of the scoliosis treatment using braces remains controversial, due to inadequacy in the selection criteria of patients and the definition of brace efficacy.…”
Section: Corrective Orthoses (Braces)mentioning
confidence: 99%
“…Several literature studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] have been conducted to evaluate the effectiveness of corrective orthoses. These studies mainly considered the selection of the effective brace type and predictive factors (compliance, curve magnitude, growth stage, body mass index, and exercise potential) that contribute to promising outcomes.…”
Section: Introductionmentioning
confidence: 99%